Fiction TV series (Journal of Parents and Teachers, 2014)
Currently, we live in the golden age for TV series, which are notably influenced by the outlook of the United States. Some decades ago, and due to the high cost of production of a Spanish series, it was preferred to buy North American series; however, now national series compete in the prime time with the American ones. The article also explains the process and the steps which are followed for developing and recording a TV series.
Keywords: Spanish series; North American series; screenwriter; production; recording.